Equity valuation of Nike, Inc. - Santos, José Eduardo Baião (2023)
Nike Inc., founded in 1964, is a North American company that, driven by its strong brand recognition, innovative product offerings, and extensive distribution network, is recognized as the global leader in the athletic footwear, apparel, equipment, and accessories industry. Currently listed on the New York Stock Exchange, since its Initial Public Offering (IPO) in 1980, the company has maintained a remarkable growth trajectory in its stock price throughout the years. This master´s dissertation primary purpose is to determine the fair value of Nike´s shares as of 31st May 2023 and subsequently, through a comparison with the market price of shares at that date, provide an investment recommendation to potential investors on whether to buy, sell or hold the stock. After thoroughly examining the relevant literature in the finance field to identify the most effective company valuation methods, the chosen methodologies that will be applied are the Free Cash Flow to the Firm, followed by a complementary method, the Relative Valuation, which will allow us to derive a more precise and well-informed final recommendation. The results derived from both Relative Valuation and the DCF Valuation method suggests that as of 31st May 2023, Nike´s shares were trading at a premium to their intrinsic value. Consequently, our final recommendation to investors is that they should sell the company´s stock.